Meningkatkan Keterampilan Orang Tua Menggunakan Video dan Buklet dalam Pertolongan Pertama untuk Kejang Demam pada Anak - Arismansyah Arismansyah; Sukmawati Sukmawati; Widi Astuti (Jurnal Sehat Mandiri, 2026)
Febrile seizures are one of the most common neurological disorders in children. The combination of videos and booklets as health education media can accommodate various learning styles and improve parental knowledge retention. This study aims to evaluate the effectiveness of educational media in the form of videos and booklets in improving parental skills related to first aid for febrile seizures in children. This pre-experimental study with a single-group pre-test/post-test design was conducted in Bima Regency, West Nusa Tenggara, Indonesia, from August 2025 to January 2026. Sixty-two parents of children aged 6 months to 5 years with a history or risk of febrile seizures were recruited using purposive sampling. The intervention consisted of a combination of educational videos and booklets containing comprehensive information on first aid for febrile seizures. Skills were assessed using a standardized observation sheet and categorized as poor, adequate, or good. Data were analyzed using the Wilcoxon Signed Rank Test. The pre-test results showed that no respondents (0%) had good skills, 61.3% had adequate skills, and 38.7% had poor skills. The post-test results showed significant improvement: 88.7% achieved good skills, 11.3% achieved sufficient skills, and 0% achieved poor skills. Statistical analysis showed a significant difference between pre-test (mean=1.61) and post-test (mean=2.89) scores (z=6.886, p=0.000). In conclusion, the combination of video and booklet was proven effective in improving first aid skills for febrile seizures.